A micro-negative pressure wound dressing and a preparation method thereof
The micro-negative pressure dressing, composed of a porous ceramic layer and a polytetrafluoroethylene membrane, solves the problem of insufficient breathability in existing technologies, enabling oxygen exchange and exudate absorption in the wound and promoting wound healing.
Patent Information
- Application Number
- CN202411956666.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-29
- Publication Date
- 2026-06-30
AI Technical Summary
Existing micro-negative pressure dressings do not take into account the issue of breathability, which affects oxygen exchange and cell metabolism in the wound, especially resulting in poor recovery of difficult-to-heal wounds.
The micro-negative pressure dressing is composed of a porous ceramic layer and a polytetrafluoroethylene membrane. The porous ceramic layer is laser-etched to form microgrooves and a hydrophilic coating, creating a gradient pore structure that combines air permeability and liquid absorption.
Without relying on negative pressure equipment, a micro-negative pressure environment is created to promote oxygen exchange and exudate absorption in the wound, thereby improving the speed and quality of wound healing.
Smart Images

Figure CN122297235A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of wound dressing technology, specifically to a micro-negative pressure dressing and its preparation method. Background Technology
[0002] Micro-negative pressure wound therapy (MSP) is an innovative technique used in wound treatment. It involves creating a micro-pressure environment at a level lower than atmospheric pressure within the wound. This MSP is achieved through specialized dressings or equipment. This micro-negative pressure promotes blood circulation in the wound, stimulates cell proliferation and migration, and aids in the growth of new tissue. Furthermore, MSP effectively drains wound exudate, reducing its accumulation and lowering the risk of infection. Simultaneously, it maintains a moderately moist wound, creating favorable conditions for healing. MSP plays a positive role in various wound treatment scenarios, including burns, chronic ulcers, and diabetic foot ulcers, and is expected to improve the speed and quality of wound healing.
[0003] Patent CN109938920A provides a micro-negative pressure foam dressing and its manufacturing method. The heat generated by the heating agent layer causes the elastic memory sheet to expand downward and compress the foam layer. After the heat dissipates, the sealing film, the contact layer and the wound surface form a closed environment, generating micro-negative pressure. It is simple to operate, low in cost and easy to carry.
[0004] Patent CN113693821A has developed a self-expanding, micro-negative pressure, highly absorbent and water-locking dressing with high absorbency, self-expansion, micro-negative pressure, water retention, good wound adhesion, good biocompatibility, and anti-infection properties. This invention can generate a stable micro-negative pressure inside the wound during the absorption process, without relying on external negative pressure equipment. It can automatically and continuously absorb exudate that is difficult to flow out from inside the wound, thus accelerating wound healing.
[0005] However, neither of the above two dressings takes into account the issue of breathability. Oxygen is essential for the aerobic metabolism of wounds, and cells also need oxygen for respiration. Good ventilation is beneficial to cell growth and repair, especially for difficult-to-heal wounds. Summary of the Invention
[0006] This invention provides a micro-negative pressure dressing and its preparation method, which solves the problem of how to construct a negative pressure dressing without using negative pressure equipment.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: A micro-negative pressure dressing and its preparation method are disclosed. The micro-negative pressure dressing consists of at least one porous ceramic layer and a polytetrafluoroethylene membrane fixed on top of the porous ceramic layer. The porous ceramic layer has a thickness of 0.5-2 mm, a pore size of 0.1-1 μm, and a porosity of 60-80%. The lower surface of the porous ceramic layer has several microgrooves with a depth of 0.1-10 μm and a width of 1-100 μm.
[0008] Furthermore, the micro-negative pressure dressing has three porous ceramic layers: the upper layer is a porous ceramic layer with a pore size of 0.6-1μm and a porosity of 70-80%; the middle layer is a porous ceramic layer with a pore size of 0.3-0.6μm and a porosity of 60-70%; and the lower layer is a porous ceramic layer with a pore size of 0.1-0.3μm and a porosity of 40-60%.
[0009] Furthermore, the porous ceramic layer is a carbon fiber alumina composite ceramic layer or a hydroxyapatite bioceramic layer.
[0010] Furthermore, the method for preparing the microgrooves is as follows: the porous ceramic layer is ultrasonically cleaned and dried with ethanol and deionized water; the porous ceramic layer is fixed on the worktable of a laser etching device for etching, using a 1064nm laser, a 100-femtosecond pulse width, an initial energy density of 2J / cm2, and controlling the scanning speed between 10-50mm / s and the repetition frequency between 100-1000Hz; after etching, it is cleaned and dried with deionized water.
[0011] Furthermore, the preparation method of the carbon fiber alumina composite ceramic layer is as follows: S1: Weigh 100g of α-Al2O3 powder, add 10g of carbon fiber to form a mixed powder, put the mixed powder into a ball mill, add 2g of ammonium polyacrylate and deionized water to make the solid-liquid ratio reach 1:2, start the ball mill and ball mill at 300r / min for 12-24h to ensure that the carbon fiber is evenly dispersed in the alumina powder. S2: Remove the slurry, add 4g of polyvinyl alcohol, stir evenly, pour the mixed slurry into a mold, and press the slurry into a 0.5-2mm thin sheet under a pressure of 50-100MPa; S3: Place the formed blank into a high-temperature sintering furnace for sintering. Heat the blank to 1500-1600℃ at a heating rate of 5-10℃ / min and hold for 2-4 hours.
[0012] Furthermore, the method for preparing the hydroxyapatite bioceramic layer is as follows: S11: Weigh 100g of hydroxyapatite powder and 30g of polyvinyl alcohol and dissolve them in deionized water. Add the polyvinyl alcohol solution to the hydroxyapatite powder. S12: Dissolve 3g of sodium hexametaphosphate in deionized water and add it to the mixture in S11; add 15g of ammonium bicarbonate, control the stirring speed at 300-600r / min, stir for 2-4h to form a uniform slurry; S13: Pour the slurry into the mold, degas it under a vacuum of -0.08~-0.1MPa, and dry the molded sample in a vacuum drying oven at 60-80℃ for 12-24h. S14: Firing the dried green body at 1000-1200℃ for 2-4 hours, with a heating rate of 5-10℃ / min.
[0013] Furthermore, the polytetrafluoroethylene film is fixed onto the porous ceramic layer using a heat sealing machine, with the heat sealing temperature set at 150-250℃ and the heat sealing time at 2-5 seconds.
[0014] Furthermore, the micro-negative pressure dressing is fixed to the skin using pressure-sensitive adhesive.
[0015] Furthermore, the upper, middle, and lower layers are fixed together by an adhesive, which is applied in dots on the porous ceramic layer.
[0016] Furthermore, the carbon fiber alumina composite ceramic layer is immersed in a 2% chitosan solution, then removed and dried in a constant temperature drying oven at 50-60℃ for 12-24 hours.
[0017] Compared with the prior art, the present invention has the following beneficial effects: This invention proposes a method for creating a micro-negative pressure environment on the wound surface without the aid of negative pressure equipment. Moreover, the dressing has good air permeability, allowing gas exchange inside and outside the dressing, which is beneficial to wound recovery. This invention utilizes the crisscrossing capillaries inside the porous ceramic layer, combined with a breathable and waterproof layer, to create a micro-negative pressure on the wound surface. At the same time, the dressing itself has good water retention capacity, keeping the wound moist and promoting wound recovery. This invention constructs a gradient dressing by assembling multiple porous ceramic layers, which can achieve both a faster liquid absorption rate and better liquid absorption capacity, thereby creating a better micro-negative pressure environment. This invention improves ceramics to give them good bending and flexibility properties, making them suitable for use on uneven wound surfaces. The porous ceramic layer of this invention has microgrooves etched on its surface and is treated with a hydrophilic coating, which increases the capillary absorption capacity and rate of the ceramic layer for exudate, enabling the establishment of micro-negative pressure more quickly and making the micro-negative pressure more stable. Attached Figure Description
[0018] Figure 1 This is a diagram showing the capillary test results of Embodiment 6 of the present invention. Detailed Implementation
[0019] To better understand the technical solution of the present invention, the embodiments of the present invention will be clearly and completely described below. Example
[0020] The micro-negative pressure dressing has at least one porous ceramic layer. In this embodiment, it is a single porous ceramic layer with a thickness of 0.5-2 mm, a pore size of 0.1-1 μm, and a porosity of 60-80%. The lower surface of the porous ceramic layer has uniformly distributed microgrooves formed by etching, with a depth of 0.1-10 μm and a width of 1-100 μm.
[0021] In this embodiment, a self-made ceramic layer was used. The ceramic layer was ultrasonically cleaned with ethanol and deionized water and then dried. The ceramic layer was then fixed on the worktable of a laser etching machine for etching, using a 1064nm laser with a pulse width of 100 femtoseconds and an initial energy density of 2J / cm². 2 The scanning speed is adjusted between 10-50 mm / s, and the repetition frequency is adjusted between 100-1000 Hz (preliminary etching can be performed first, and then the etching effect can be observed under an optical microscope. The parameters can be adjusted according to the etching effect before etching again until the expected target is achieved); after etching, it is cleaned with deionized water and dried.
[0022] The method for preparing the self-made ceramic in this embodiment is as follows: S1: Weigh 100g of α-Al2O3 powder, add 10g of carbon fiber to form a mixed powder, put the mixed powder into a ball mill, add 2g of ammonium polyacrylate and deionized water to make the solid-liquid ratio reach 1:2, start the ball mill and ball mill at 300r / min for 12-24h to ensure that the carbon fiber is evenly dispersed in the alumina powder. S2: Remove the slurry, add 4g of polyvinyl alcohol, stir evenly, pour the mixed slurry into a mold, and press the slurry into a 0.5-2mm thin sheet under a pressure of 50-100MPa; S3: Place the formed blank into a high-temperature sintering furnace for sintering. Heat the blank to 1500-1600℃ at a heating rate of 5-10℃ / min and hold for 2-4 hours.
[0023] The porous ceramic layer obtained by the above method has a pore size of 0.3-0.7μm and a porosity of about 70%. In this embodiment, the self-made ceramic was subjected to bending test, and the bending strength was 400-600MPa. It has bending flexibility and can be bent to fit the wound surface.
[0024] In addition to the porous ceramic layer, the micro-negative pressure dressing has a polytetrafluoroethylene (PTFE) film on its upper surface. The PTFE film is fixed to the porous ceramic layer using a heat sealing machine. The heat sealing temperature is set at 150-250℃, and the heat sealing time is 2-5 seconds. The PTFE film is larger than the porous ceramic layer, and the excess portion around its edges is fixed to the skin using pressure-sensitive adhesive. The edges of the lower surface of the porous ceramic layer are also fixed using pressure-sensitive adhesive.
[0025] Working principle: After the micro-negative pressure dressing is attached and fixed to the skin, the wound exudate will be quickly guided into the interior of the porous ceramic layer through the micro-grooves. The porous ceramic layer has a large number of capillary channels, and the exudate is quickly drawn into the pores. As the exudate fills the pores, the gas inside the pores is squeezed out and slowly discharged through the outer polytetrafluoroethylene membrane. Due to the continuous absorption of liquid and the discharge of gas, a micro-negative pressure environment is formed inside the dressing. Example
[0026] Based on Example 1, the porous ceramic layer is composed of multiple layers. This example shows a micro-negative pressure dressing composed of three porous ceramic layers. The inner layer (with microgrooves on the lower surface) is a porous ceramic layer with a pore size of 0.1-0.3 μm and a porosity of 40-60%; the middle layer is a porous ceramic layer with a pore size of 0.3-0.6 μm and a porosity of 60-70%; and the outer layer (close to the polytetrafluoroethylene membrane) is a porous ceramic layer with a pore size of 0.6-1 μm and a porosity of 70-80%. The thickness of each layer is 0.5-2 mm and can be adjusted according to the amount of exudate from the wound.
[0027] The layers are fixed together with an adhesive, which is applied thinly to the edges of the porous ceramic layers, or to parts of the edges and interior; a dot-application method is preferred. After bonding, the number of gas diffusion channels between the layers increases, which helps to accelerate the formation of micro-negative pressure and maintain a stable negative pressure state.
[0028] This embodiment forms a gradient pore structure. The inner layer has a smaller pore size, which can quickly absorb the liquid when it comes into contact with wound exudate using strong capillary action. At the same time, the porosity of the inner layer can provide sufficient liquid storage space while maintaining sufficient strength. The pore size gradually increases from the middle layer to the outer layer, which helps the liquid to be transferred outward better and improves the exchange efficiency of liquid and gas. Example
[0029] Based on Example 1, the porous ceramic layer uses a hydroxyapatite bioceramic layer, which is prepared by the following method: S11: Weigh 100g of hydroxyapatite powder and 30g of polyvinyl alcohol and dissolve them in deionized water. Add the polyvinyl alcohol solution to the hydroxyapatite powder. S12: Dissolve 3g of sodium hexametaphosphate in deionized water and add it to the mixture in S11; add 15g of ammonium bicarbonate, control the stirring speed at 300-600r / min, stir for 2-4h to form a uniform slurry; S13: Pour the slurry into the mold, degas it under a vacuum of -0.08~-0.1MPa, and dry the molded sample in a vacuum drying oven at 60-80℃ for 12-24h. S14: Firing the dried green body at 1000-1200℃ for 2-4 hours, with a heating rate of 5-10℃ / min.
[0030] The hydroxyapatite bioceramic layer prepared by the above method can be bent 5-10 mm, has a pore size of 0.1-10 μm, and a porosity of about 80%.
[0031] The micro-negative pressure dressing of this embodiment expands the clinical application scenarios. Hydroxyapatite does not cause immune rejection or inflammatory reactions, providing a good biological environment for wound healing. Hydroxyapatite also has the effect of inducing bone regeneration, and it can be used for deep burns or traumatic wounds with exposed bone. Example
[0032] Based on Example 1, a coating treatment was applied to the surface of the porous ceramic layer. The porous ceramic layer was immersed in a 2% chitosan solution for 2 hours, and then the porous ceramic sheet was removed and placed in a constant temperature drying oven at 50-60°C for 12-24 hours.
[0033] After treatment, a hydrophilic coating is formed on the surface of the porous ceramic layer, which enhances the attraction and flow rate of the exudate. Example
[0034] This embodiment is a contact angle measurement experiment of Examples 1-4, in which a contact angle measuring instrument is used to measure the water contact angle.
[0035] Contact angle Example 1 78.23° Example 2 74.98° Example 3 63.17° Example 4 38.61° Tests showed that the contact angle of Examples 1-4 was <90°, indicating hydrophilicity, which facilitates the flow of exudate into the dressing. Furthermore, the hydrophilic coating treatment resulted in even better hydrophilicity, which is more conducive to the faster and more stable formation of micro-negative pressure. Example
[0036] This embodiment is a capillary test conducted on Embodiments 1, 3, and 4. The specific operation is as follows: The porous ceramic layer (2mm thick) in the micro-negative pressure dressing was cut into 5cm square samples. A 1cm deep solution of red ink (red ink to water ratio 1:10) was poured into the culture medium. The sample was placed horizontally on the surface of the red ink solution. Timing was started, and a video of the liquid rising in the sample was recorded using a camera. Screenshots were taken every 0.5-1 minute, and the height of the liquid rising in the sample was recorded. The data was then plotted as a curve showing the change in the rising height over time. The results are shown below. Figure 1 As shown. Example
[0037] This embodiment is a micro-negative pressure experiment conducted in Examples 1-4. Pressure sensors were installed at the center and four corners of the lower surface of the micro-negative pressure dressing. The dressing was then adhered and fixed to the simulated wound, and a negative pressure source was connected to calibrate the pressure sensors. Simulated human tissue fluid (0.5-1% human serum albumin added to a 0.9% NaCl solution) was added to the simulated wound site. The dressing was re-fixed, and the pressure sensor data was recorded. The experimental results show that in the initial 1-5 minutes, the pressure rapidly decreased from 0 kPa to -2 kPa to -5 kPa. In the following 10-20 minutes, the pressure gradually decreased to -6 kPa to -7 kPa. After 20-30 minutes, the pressure stabilized at -7 kPa to -8 kPa. The pressure stabilization time can reach 24-48 hours. For example, in an environment with normal temperature and 70% relative humidity, the pressure stabilization time of a 2 mm thick sample from Example 1 was approximately 26 hours.
[0038] The above embodiments are only some embodiments of the present invention. It should be understood that, under the inventive concept of the present invention, all technical solutions obtained by those skilled in the art through equivalent substitution or equivalent substitution fall within the protection scope of the present invention.
Claims
1. A micro-negative pressure dressing and its preparation method, characterized in that, The micro-negative pressure dressing consists of at least one porous ceramic layer and a polytetrafluoroethylene membrane fixed on top of the porous ceramic layer. The porous ceramic layer has a thickness of 0.5-2 mm, a pore size of 0.1-1 μm, and a porosity of 60-80%. The lower surface of the porous ceramic layer has several microgrooves with a depth of 0.1-10 μm and a width of 1-100 μm.
2. The micro-negative pressure dressing and its preparation method according to claim 1, characterized in that, The micro-negative pressure dressing has three porous ceramic layers: the upper layer has a pore size of 0.6-1μm and a porosity of 70-80%; the middle layer has a pore size of 0.3-0.6μm and a porosity of 60-70%; and the lower layer has a pore size of 0.1-0.3μm and a porosity of 40-60%.
3. A micro-negative pressure dressing and its preparation method according to claim 1 or 2, characterized in that, The porous ceramic layer is either a carbon fiber alumina composite ceramic layer or a hydroxyapatite bioceramic layer.
4. The micro-negative pressure dressing and its preparation method according to claim 1, characterized in that, The method for preparing the microgrooves is as follows: the porous ceramic layer is ultrasonically cleaned and dried with ethanol and deionized water; the porous ceramic layer is fixed on the worktable of a laser etching device for etching, using a 1064nm laser with a pulse width of 100 femtoseconds and an initial energy density of 2J / cm². 2 The scanning speed is controlled between 10-50 mm / s, and the repetition frequency is between 100-1000 Hz. After etching, the surface is cleaned with deionized water and dried.
5. The micro-negative pressure dressing and its preparation method according to claim 3, characterized in that, The method for preparing the carbon fiber alumina composite ceramic layer is as follows: S1: Weigh 100g of α-Al2O3 powder, add 10g of carbon fiber to form a mixed powder, put the mixed powder into a ball mill, add 2g of ammonium polyacrylate and deionized water to make the solid-liquid ratio reach 1:2, start the ball mill and ball mill at 300r / min for 12-24h to ensure that the carbon fiber is evenly dispersed in the alumina powder. S2: Remove the slurry, add 4g of polyvinyl alcohol, stir evenly, pour the mixed slurry into a mold, and press the slurry into a 0.5-2mm thin sheet under a pressure of 50-100MPa; S3: Place the formed blank into a high-temperature sintering furnace for sintering. Heat the blank to 1500-1600℃ at a heating rate of 5-10℃ / min and hold for 2-4 hours.
6. The micro-negative pressure dressing and its preparation method according to claim 3, characterized in that, The method for preparing the hydroxyapatite bioceramic layer is as follows: S11: Weigh 100g of hydroxyapatite powder and 30g of polyvinyl alcohol and dissolve them in deionized water. Add the polyvinyl alcohol solution to the hydroxyapatite powder. S12: Dissolve 3g of sodium hexametaphosphate in deionized water and add it to the mixture in S11; add 15g of ammonium bicarbonate, control the stirring speed at 300-600r / min, stir for 2-4h to form a uniform slurry; S13: Pour the slurry into the mold, degas it under a vacuum of -0.08~-0.1MPa, and dry the molded sample in a vacuum drying oven at 60-80℃ for 12-24h. S14: Firing the dried green body at 1000-1200℃ for 2-4 hours, with a heating rate of 5-10℃ / min.
7. The micro-negative pressure dressing and its preparation method according to claim 1, characterized in that, The polytetrafluoroethylene film is fixed onto the porous ceramic layer by a heat sealing machine. The heat sealing temperature is set at 150-250℃ and the heat sealing time is 2-5 seconds.
8. The micro-negative pressure dressing and its preparation method according to claim 1, characterized in that, The micro-negative pressure dressing is fixed to the skin using pressure-sensitive adhesive.
9. The micro-negative pressure dressing and its preparation method according to claim 2, characterized in that, The upper, middle and lower layers are fixed together by an adhesive, which is applied in dots on the porous ceramic layer.
10. The micro-negative pressure dressing and its preparation method according to claim 5, characterized in that, The carbon fiber alumina composite ceramic layer was immersed in a 2% chitosan solution, then removed and dried in a constant temperature drying oven at 50-60℃ for 12-24 hours.
Citation Information
Patent Citations
Negative micro-pressure foam dressing and manufacturing method thereof
CN109938920A
Self-expanding super-water-absorbing and water-locking micro-negative-pressure dressing and preparation method thereof
CN113693821A
